Electrical Distribution Network Challenges of Rapid EV Adoption in Rural Areas Surrounding Urban Centres: Case Study in Ireland - Caulfield, Brian; Singh, Abhilash; Mc Closkey, David (My University, 2026)
Rural regions, with lower population density, typically show higher car dependency leading to greater vehicle ownership, longer trips and higher travel frequencies. As a result, transport electrification of rural areas will strongly influence per-capita carbon reduction targets. This work considers capacity issues on low voltage distribution networks for uptake of large penetration level of electrified transport in rural areas. We use Ireland as a particular case study as 36% of the population live in rural areas, but account for ~55% of transport emissions. We synthesize EV charging load profiles for typical rural residential clusters under increasing EV penetration levels up to 100%. Results indicate that synchronized home charging during off-peak hours (02:00–04:00) is a key issue leading to voltage drops of up to 12% from 230 V and substantial transformer temperature rises and cycling. Smart charging including scheduling, queuing services, and flexible demand strategies offers significant potential to mitigate thermal stress, reducing peak temperatures by almost 80◦C depending on the scenario and defer costly grid reinforcements. Urgent collaboration between policy makers, EV charger manufacturers and aggregators, and distribution system operators, and energy retailers is required to implement flexibility and offset future costs. Typically considered in the context of dense urban areas, we demonstrate that smart charging can also be of practical benefit in rural regions.
PUBLISHED
Keywords: Electric vehicles (EVs); Low-voltage distribution network; Rural electrification; Grid capacity constraints; Smart charging; Renewable integration; Sustainable energy transition; Smart & Sustainable Planet; Environmental aspects of transportation; Transport